1982
DOI: 10.1080/03015521.1982.10427834
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Romney, Coopworth, and Perendale breeds on lambskin leather quality

Abstract: Skins from 5-month-old wether lambs reared under hill country conditions were processed and evaluated in terms of their impact on the New Zealand tanning industry. Breeds examined in this work were the Coopworth, Perendale, and Romney. The Perendale produced the most desirable wool characteristics for the production of leather tanned with the wool on. Although the Perendale showed the poorest grain leather qualities, the grain layer itself was stronger and more elastic than in the Romney and the Coopworth skin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

1983
1983
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 3 publications
1
10
0
Order By: Relevance
“…This and other trials (Hughes et al 1978;Passman & Dalton 1982;Passman & Sumner 1983) have shown significant breed differences in aspects of leather quality, particularly suitability for woolon leather production. Present monetary returns from skins, however, are insufficient to justify farmers choosing a specific breed or slaughter time solely on the grounds of skin attributes.…”
Section: Discussionsupporting
confidence: 50%
See 3 more Smart Citations
“…This and other trials (Hughes et al 1978;Passman & Dalton 1982;Passman & Sumner 1983) have shown significant breed differences in aspects of leather quality, particularly suitability for woolon leather production. Present monetary returns from skins, however, are insufficient to justify farmers choosing a specific breed or slaughter time solely on the grounds of skin attributes.…”
Section: Discussionsupporting
confidence: 50%
“…Leather production After slaughter the skins were washed in cold water, salted, and held for a month before being sent to the New Zealand Leather and Shoe Research Association's pilot tannery. Tanning procedures were similar to those described previously (Passman & Dalton 1982).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A degree of correspondence across localities on a skin cannot be regarded as indicative of selection response in such traits. However, breed differences in the physical leather characteristics of sheep suggest the possibility of genetic influences upon leather quality (Passman & Dalton, 1982;Passman & Sumner, 1987;Holst et al, 1997;Snyman & Jackson-Moss, 2000). Further research in this area is indicated to explore the possibility of altering physical skin and nodule parameters by genetic selection.…”
Section: Discussionmentioning
confidence: 99%